In vitro Assessment of Paclitaxel-loaded Niosome Nanoparticles and Their Cytotoxic Effects on the Ovarian Cancer Cell Line A2780CP - Khaje, Nasrin; Salehan, Fatemeh; Shakiba, Davoud; Shabestari, Aida Mohammadiun; Shoarishoar, Seyedeh Shahed (Asian Pacific Journal of Cancer Biology, 2024)
Background: One of the major concerns in contemporary medical science is the issue of cancer, with ovarian cancer being a significant contributor to cancer-related deaths. A key challenge in treating ovarian cancer is its initial responsiveness followed by resistance to paclitaxel therapy. However, recent advances in nanotechnology, particularly drug delivery systems like niosomes, offer promising solutions. Methods: Researchers fabricated nanoparticles via the ether injection approach and analyzed them for particle dimensions, surface charge, and medication release characteristics. Subsequently, they employed A2780CP ovarian cancer cell lines to evaluate the impact of nanodrug using an MTT assay. Results: The average particle size was reported at 190.3 ± 20.6 nm, with a zeta potential of -18.9 ± 2.7 mV. Notably, high encapsulation proficiency (87.6 ± 32%) verified the successfulness of the applied technique. Moreover, the cytotoxicity assessment demonstrated enhanced efficacy of nanodrug over free carboplatin when targeting A2780CP cell lines (P < 0.05). Conclusion: these findings suggest that pegylated liposomal nanocarriers could be effective carriers for delivering paclitaxel to A2780CP ovarian cancer cell lines.